La autoestima y la asertividad en los estudiantes de la escuela de educación Básica “San Felipe Neri” Riobamba- Chimborazo - Herrera Flores, Joel David (2023)
The objective of this work is to determine the influence of self-esteem on the assertiveness of the students of the School of Basic Education "San Felipe Neri," this research will be beneficial for society and the individuals who can read it. It will contribute to the solution of the problem that is being treated in the same context. Knowing about assertiveness and how it is influenced by self-esteem is of great importance for the students with whom we are going to work, as well as knowing the relationship between self-esteem and assertiveness is of great interest. The research responds to the quantitative approach because we will use psychometric techniques with the appropriate instrument. It is correlational because, in the end, we will analyze whether or not there is a correlation between the study variables. A non-probabilistic sample of eighty-two 9th and 10th-year students of EGB will be used. The data were interpreted using the techniques suggested by the approach according to the instrument applied. For the processing of the data, objectivity was used with the Excel program, complemented by the elaboration of statistics, such as tables and pies, from the analysis of each question expressed in each instrument. Thus the results obtained globally according to the participation of the students verified that there is low self-esteem in the students. In this way, they also lack assertiveness in their social relations with students and teachers. The COOPERSMITH self-esteem scale is a 58-item self-reporting instrument in which the subject reads and decides whether that statement is "the same as me" or "different from me." It consists of 50 items and a lying scale of 8 items. For assertiveness, we use the RATHUS assertiveness scale consisting of 30 items (questions) with six response options (ranging from very characteristic of me to not characteristic of me at all). This test gives us a final score as well as a percentile.